Dekonstruksi Stigma Tradisional: Pembingkaian Pertanian sebagai Peluang Bisnis Prospektif dalam Program "Jejak Si Gundul" - Ni Kadek Aria Candra Dewi; Yogaprasta Adi Nugraha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
The declining interest in the agricultural sector poses a significant threat to food sovereignty. This study aims to analyze how mass media constructs agricultural narratives through the television program "Jejak Si Gundul" to counter the negative stigma surrounding the agrarian sector. Employing a qualitative approach with Zhongdang Pan and Gerald M. Kosicki's framing analysis, the research examines media texts across four dimensions: syntactic, script, thematic, and rhetorical. Data were gathered through participatory observation of selected episodes, in-depth interviews, and documentation. The findings reveal that "Jejak Si Gundul" consistently frames agriculture and rural life as prospective and innovative sectors. Syntactically and rhetorically, the use of narratives highlighting local wisdom and economic potential effectively transforms the image of agriculture from a marginal sector into a sustainable lifestyle. The thematic analysis shows a deconstruction of negative agricultural stereotypes by emphasizing environmental sustainability. This study concludes that positive media framing plays a crucial role in constructing social realities that can inspire the younger generation to re-engage in agricultural development. Kata Kunci: Framing, Komunikasi Massa, Pertanian, Persepsi.